Metal removal from Municipal Solid Waste Incineration fly ash: A comparison between chemical leaching and bioleaching. (February 2017) - Funari, V.; Mäkinen, J.; Salminen, J.; Braga, R.; Dinelli, E.; Revitzer, H.
Highlights: H2 SO4 leaching and bioleaching of incineration fly ash are compared. Both processes resulted in satisfactory yields (>85%) for Al, Mg, Mn, Zn, Cu. Bioleaching showed a significant selectivity for toxic elements and lanthanides. Bioleaching halved the use of mineral acid with respect to H2 SO4 leaching. Bioleaching can be an affordable approach after appropriate optimisation. Abstract: Bio- and hydrometallurgical experimental setups at 2-l reactor scale for the processing of fly ash from municipal waste incinerators were explored. We aimed to compare chemical H2 SO4 leaching and bioleaching; the latter involved the use of H2 SO4 and a mixed culture of acidophilic bacteria. The leaching yields of several elements, including some of those considered as critical (Mg, Co, Ce, Cr, Ga, Nb, Nd, Sb and Sm), are provided. At the end of the experiments, both leaching methods resulted in comparable yields for Mg and Zn (>90%), Al and Mn (>85%), Cr (∼65%), Ga (∼60%), and Ce (∼50%). Chemical leaching showed the best yields for Cu (95%), Fe (91%), and Ni (93%), whereas bioleaching was effective for Nd (76%), Pb (59%), and Co (55%). The two leaching methods generated solids of different quality with respect to the original material as we removed and significantly reduced the metals amounts, and enriched solutions where metals can be recovered for example as mixed salts for further treatment. Compared to chemical leaching the bioleaching halved the use of H2 SO4, i.e., a part of agent costs, as a likely consequence of bio-produced acid and improved metal solubility.